Oray-Orayan dalam Perspektif Struktural: Menelisik Tradisi Lisan dan Kearifan Lokal Kota Cimahi - Ayu Widiyani Sigid; Yulianeta; Tedi Permadi; Khairul Fuad (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2026)
This study was motivated by the decline of traditional games in urban areas, which has hindered the process of cultural value inheritance. The study focused on the narratives found in the children's game